CLASSICAL MECHANICS AND QUANTUM MECHANICS : an historic-axiomatic approach. - PETER ENDERS (BENTHAM Science PUBLISHER, 2019)
This unique textbook presents a novel, axiomatic pedagogical path from classical to quantum physics. Readers are introduced to the description of classical mechanics, which rests on Euler's and Helmholtz's rather than Newton's or Hamilton's representations. Special attention is given to the common attributes rather than to the differences between classical and quantum mechanics. Readers will also learn about Schrödinger's forgotten demands on quantization, his equation, Einstein's idea of 'quantization as selection problem'. The Schrödinger equation is derived without any assumptions about the.